Land subsidence in Beijing: response to the joint influence of the South-to-North Water Diversion Project and ecological water replenishment, observed by satellite radar interferometry - Min Shi; Mingliang Gao; Zheng Chen; Mingyuan Lyu; Huili Gong; Yuanzheng Zhai; Yun Pan (GIScience & Remote Sensing)
The South-to-North Water Diversion Project Middle Route (SNWD-MR) annually diverts hundreds of millions of cubic meters of water from the Danjiangkou Reservoir to Beijing, significantly impacting the regional groundwater cycle. To conserve water resources, the government has implemented ecological water replenishment (EWR) in some water systems. This study aimed to study the coupled process of groundwater dynamics and land subsidence (LS) in Yongding River (YDR) basin (Beijing section) following the implementation of the SNWD-MR and EWR. First, an Interferometric Synthetic Aperture Radar (InSAR) time series technique was used to detect spatial and temporal distributions of surface displacement between 2015 and 2020 based on satellite images from Sentinel-1A/B. The results indicated a predominant LS deceleration trend during the InSAR observation period. The area with subsidence velocity below 20 mm/yr decreased significantly by 18.6% after SNWD-MR and EWR (from 2016 to 2020). Then, groundwater level fluctuations during the InSAR observation period were analyzed using groundwater measurement well data. Over 60% of these wells showed a rebound in groundwater levels after the implementation of SNWD-MR and EWR. The polynomial distribution lag model (PDL) revealed the association between LS and groundwater level changes, depicting both short- and long-term lag effect. The results showed significant spatial and temporal heterogeneity on the short- and long-term response between groundwater level change and regional subsidence. In addition, we calculated the differential subsidence slope based on the InSAR-derived LS and analyzed its impact on the river slope after SNWD-MR and EWR. The results show that two sections with significant severe differential subsidence slope occur between 0 and 14,000 m and between 54,000 and 78,000 m along the YDR. The slope change caused by LS may reduce the conveyance capacity of surface canals, and more attention should be paid in those two sections. These findings have an important scientific significance for management strategy for LS control against the background of SNWD-MR and EWR.